Perception Regarding Swine Flu Among School Teacher in Inaruwa Municipality of Eastern Nepal - Uprety, Samyog Uprety; Limbu, NPM; Poudel, M; Ghimire, A; Khanal, VK; Baral, DD (Birat Journal of Health Sciences, 2017)
Introduction Swine flu is an acute respiratory viral disease, caused by a strain of the influenza type A virus known as H1N1. Currently swine flu is spreading rapidly in India with a regular threat of it being spread to Nepal owing to the open borders. Objecive The objective of this study was to assess the knowledge, attiude and practice on different aspects of Swine Flu. Methodology This is cross-sectional study conducted in Inaruwa municipality of Sunsari district from 1st March to 10th April, 2015. A total of 31 schools (21 private and 10 public) were identified in the municipality out of which 16 were randomly chosen for the study. Results Total sample size was 260 school teachers. Majority of the respondents belong to the age group 30-39 years, about 72 % were male and 86% thought that it is a preventable disease. It was observed that females had a better attitude towards preventive measures of swine flu as compared to the males (p<0.023), but males had beertter practices as compared to the females (p<0.001). Conclusion The preventation on practice for swine flu was not adequate. Despite having acceptable knowledge and attitude positive practices needs to be encouraged. The teachers should be well informed about the earliest appearing symptoms of swine flu. So that they can closely monitor the students and can recommend the students for medical checkup on appearance of the symptoms. Birat Journal of Health Sciences Vol.2/No.1/Issue 2/ Jan - April 2017, Page: 150-155